Crystal density of CaS under pressure up to 40 GPa - Bioud, Nadhira; Mezouar, Rabie (International Journal of Advanced Chemistry, 2022)
Based on the experimental ground state parameters reported in the literature (Luo et al., Phys. Rev. B 50 (1994)16232-16237); in the present work we reproduce the variation in the volume with the pressure up to 40 GPa for calcium sulfide (CaS) compound, which criticized in cubic rock-salt structure. We used two different models of equation of state (EOS); the fist is the model of Vinet, while the second one is the EOS Murnaghan’s model. We studied also the effect of the pressure on the crystal density. We established some analytical models relating the volume with the pressure, as well as the crystal density with the pressure.Finally, we predicted the melting point, the Debye temperature and the sound velocity of CaS material, which are 1202.2 K, 423.7 K, and 4049.5 m/s, respectively.